An Investigation Into The Speak Now Series: Internal And External Characteristic - Jihad Hasan Azeez, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main thrust of the present study was to explore the Speak Now Series in terms of external and internal characteristics. To this end, Littlejohn’s (1998) checklist was utilized in order to investigate the series in terms of Task Analysis Sheets (TAS) and Design. The results of the study indicated that the series has its own strengths among which form-meaning relationships, developing communicative competence, consistency and continuity, the visual and auditory features supplemented with oral-emphasized skills are worth mentioning. Exploring the design of the series, on the other hand, showed that the themes covered in the series are the most related, necessary and crucial ones which motivate the learners to engage in the presented activities. Furthermore, The Speak Now series is apparently suffering from the presented speaking tasks, which do not seem to be challenging and motivating enough. The series also does not engage the learners and teachers in the learning and teaching processes.